2021
DOI: 10.1007/s00127-021-02170-1
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for family reunification and the risk of mental disorders among refugee fathers: a 24-year longitudinal cohort study from Denmark

Abstract: Purpose To examine whether family separation caused by prolonged waiting for family reunification is associated with the risk of mental disorders among refugee fathers. Method Based on full-population Danish registry data covering 1995–2015, we mapped arrival patterns among nuclear refugee family members resettled in Denmark (n = 76,776) and established a cohort of refugee fathers (n = 6176) who all arrived alone and later obtained family reunification wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…One study in Germany found that family separation among refugees contributes to worse mental health conditions ( 40 ). A longitudinal cohort study in Denmark found that refugee men awaiting reunification with their wives and children were at an increased risk of mental disorders ( 41 ). Additionally, not only are adverse psychosocial experiences involved in the onset of hypertension, parental separation has been associated with the onset of hypertension in women separated from their parents ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study in Germany found that family separation among refugees contributes to worse mental health conditions ( 40 ). A longitudinal cohort study in Denmark found that refugee men awaiting reunification with their wives and children were at an increased risk of mental disorders ( 41 ). Additionally, not only are adverse psychosocial experiences involved in the onset of hypertension, parental separation has been associated with the onset of hypertension in women separated from their parents ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the majority of our study population had resided in the U.S. for a significant amount of time. Indeed, the length of time can impact the strength of the relationship between separation and negative health outcomes (Hvidtfeldt et al, 2021). Less is known about the specific disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These may include poverty, lack of employment opportunities, food insecurity, conflict, violence, and natural disasters 122,123 . The act of migrating also involves displacement and dislocation, which may be traumatic, compromise personal safety, create uncertainty and stress, and involve prolonged separation from family 124‐126 , and high levels of risk to life or personal safety 124 . For example, between 40 and 90% of asylum seekers report traumatic experiences during migration 118,122,127 , including violence, exploitation, and detainment during the asylum‐seeking process 128 .…”
Section: Social Determinants That Impact Mental Health and Disorder: ...mentioning
confidence: 99%